Efektifitas Senam Hamil Terhadap Kemudahan Proses Persalinan Di Puskesmas Sukawali Kabupaten Tangerang - Sumiyati; Futriani, Elfira Sri (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Pregnancy exercise is an exercise program for healthy pregnant women to prepare the mother's physical condition by maintaining the condition of the muscles and joints that play a role in the birth process, as well as preparing the mother's psychological condition, especially increasing self-confidence in facing childbirth. Pregnancy exercise provides benefits to the biomotor components of the muscles being trained. Regular exercise or exercise during pregnancy is associated with giving birth on time. Another benefit of pregnancy exercise is that it plays a direct role in reducing morbidity and mortality rates for mothers and babies born. Methods: Quantitative research methods. The population to be studied is pregnant women at the Sukawali Community Health Center, Tangerang Regency. The sampling technique used in this research was purposive sampling. The inclusion criteria in this sampling were: 1) Pregnant women. 2) Give birth at the Sukawali Community Health Center. 3) Live at home with husband. 4) Willing to be a respondent. The total sample was 44 pregnant women. The research instrument is a questionnaire Results: The results of the analysis of the relationship between pregnancy exercise and the smoothness of the birth process, it was found that of the 30 mothers who took part in the exercise process, 23 people (52.3%) experienced a smooth delivery and 7 people (15.9%) did not have a smooth birth. Meanwhile, of the 14 people who did not participate in exercise, 14 people (31.8%) experienced smooth labor and no one (0.0%) had an uneventful birth. The results of the Chi Square test by looking at the continuity correction obtained a P value of 0.049 (<0.05) Conclusion: There is a significant relationship between the implementation of pregnancy exercise and the smooth delivery process at the Sukawali Community Health Center in 2023, which means that pregnancy exercise is effective in the smooth delivery process.